Barriers to Access to Payment Systems and Proposed Actions : Special-Purpose Note - Global Remittances Working Group (World Bank, Washington, DC, 2015)
This paper analyzes the difficulties for nonbank RSPs in their indirect access to the domestic payment system infrastructure. It presents the background (section three) and the current situation, giving examples from a few key sending markets (section four). The main factors underlying the current situation are outlined (section five), and several potential pragmatic solutions are presented as a basis for further discussion along with implementable action plans (section six). The paper concludes with possible next steps (section seven).